2008
DOI: 10.1074/jbc.m801547200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase G-dependent Cardioprotective Mechanism of Phosphodiesterase-5 Inhibition Involves Phosphorylation of ERK and GSK3β

Abstract: Sildenafil, a potent inhibitor of phosphodiesterase-5 (PDE-5) induces powerful protection against myocardial ischemiareperfusion injury. PDE-5 inhibition increases cGMP levels that activate cGMP-dependent protein kinase (PKG). However, the cause and effect relationship of PKG in sildenafil-induced cardioprotection and the downstream targets of PKG remain unclear. Adult ventricular myocytes were treated with sildenafil and subjected to simulated ischemia and reoxygenation. Sildenafil treatment significantly dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
161
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(171 citation statements)
references
References 55 publications
8
161
0
2
Order By: Relevance
“…In addition to regulating the expression of antiapoptotic genes, other mechanisms may also contribute to the antiapoptotic effect of PKG on renal IR, such as PKG-mediated direct phosphorylation of NF-B proteins (19,24) or PKG-mediated opening of mitochondria K ATP channels and decreases in calcium influx (36). Recently, the survival signaling such as ERK or Akt has been shown to be phosphorylated by PKG in cardiomyocytes and plays a role in PKG-induced cytoprotection (13). Consistent with these reports, we found that the levels of phosphorylated ERK in the kidney were increased to a greater extent in the IR group of transgenic mice than in wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to regulating the expression of antiapoptotic genes, other mechanisms may also contribute to the antiapoptotic effect of PKG on renal IR, such as PKG-mediated direct phosphorylation of NF-B proteins (19,24) or PKG-mediated opening of mitochondria K ATP channels and decreases in calcium influx (36). Recently, the survival signaling such as ERK or Akt has been shown to be phosphorylated by PKG in cardiomyocytes and plays a role in PKG-induced cytoprotection (13). Consistent with these reports, we found that the levels of phosphorylated ERK in the kidney were increased to a greater extent in the IR group of transgenic mice than in wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…PKG-I is expressed in vascular smooth muscle cells, cardiomyocytes, endothelial cells, mesangial cells, renal tubular cells, macrophages, and other cell types (9). Recent studies demonstrated the protective effect of the cGMP/PKG signaling pathway on IR injury in the heart as well as in cardiomyocytes through several mechanisms such as regulation of mitochondria K ATP channels or enhanced phosphorylation of Akt, ERK, and glycogen synthase kinase (GSK)-3␤ (5,11,13) . However, whether PKG displays a protective effect on kidney IR injury is unknown.…”
mentioning
confidence: 99%
“…For example, evidence shows that PKG can protect cells from IR injury by activating signaling cascades that delay mPTP opening [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…cGMP then activates PKG, which opens the mitoKATP that prevents the loss of ionic gradients and allows for continued ATP production and calcium transport [199,200] . The protective effects of sildenafil are also associated with PKG-dependent phosphorylation of ERK and GSK3β [212] . The role of mitoKATP is essential since the cardioprotective effects of PDE5 inhibitors can be abrogated by the putative blocker of mitoKATP, 5-HD [197,202] .…”
Section: Effects Of Pde5 Inhibitors On Myocardial Ischemiareperfusionmentioning
confidence: 99%